2002
DOI: 10.1111/1467-8551.00227
|View full text |Cite
|
Sign up to set email alerts
|

How Issues Become (Re)constructed in the Media: Discursive Practices in the AstraZeneca Merger

Abstract: In this article, we put forward a novel way of exploring difference and contradiction in merging organizations. We examine how the media (re)constructs meanings in a major cross‐border merger. Based on an analysis of press coverage, we attempt to specify and illustrate how particular issues are (re)constructed in media texts through interpretations of ‘winning’ and ‘losing’. We also show how specific discourses are drawn on in this (re)construction. In the merger studied, discourse based on economic and financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 43 publications
0
110
0
7
Order By: Relevance
“…Notwithstanding the broader literature on power and politics in organizations (e.g., Eisenhardt & Bourgeois, 1988;Pfeffer & Moore, 1980;Clegg, Courpasson & Phillips, 2006), extant work has only scratched the surface of politics in PMI (Vaara, 2003;Tienari & Vaara, 2012). Prior work suggests that socio-political factors affect interactions between key actors in PMI (e.g., Clark & Geppert, 2011), and that PMI may be linked with broader cultural or societal power relationships and political processes (Hellgren et al, 2002;Tienari, Vaara & Björkman, 2003;Tienari et al, 2005). However, it is notable that current work has mainly focused on the causes and consequences of conflicts in the post-acquisition company.…”
Section: Decision-makingmentioning
confidence: 99%
“…Notwithstanding the broader literature on power and politics in organizations (e.g., Eisenhardt & Bourgeois, 1988;Pfeffer & Moore, 1980;Clegg, Courpasson & Phillips, 2006), extant work has only scratched the surface of politics in PMI (Vaara, 2003;Tienari & Vaara, 2012). Prior work suggests that socio-political factors affect interactions between key actors in PMI (e.g., Clark & Geppert, 2011), and that PMI may be linked with broader cultural or societal power relationships and political processes (Hellgren et al, 2002;Tienari, Vaara & Björkman, 2003;Tienari et al, 2005). However, it is notable that current work has mainly focused on the causes and consequences of conflicts in the post-acquisition company.…”
Section: Decision-makingmentioning
confidence: 99%
“…The pharmaceutical industry has itself gone through a series of mergers and acquisitions (Schweizer 2005). It appears that in cases such as Astra-Zeneca (Hellgren et al 2002) or Sanofi-Aventis (Mittra 2006), specific synergies have played a central role in official legitimation, whereas other concerns have been silenced. Without going any further, it seems that examples of -talked up‖ synergies and consequent integration problems are only too easy to find.…”
Section: Dynamicsmentioning
confidence: 99%
“…These studies have shown how the media constructs certain kinds of images of mergers and acquisitions, thereby forming an important arena for the legitimation of these deals (Hirsch 1986, Schneider and Dunbar 1992, Hellgren et al 2002, Kitchener 2003, Tienari et al 2003, Comtois et al 2004, Leonardi and Jackson 2004. On one hand, the media can pick up specific issues and thus promote or question the legitimacy of the merger or acquisition (Hellgren et al 2002, Comtois et al 2004, Leonardi and Jackson 2004. On the other hand, the actors involved can also use the media as an arena for -discursive strategizing,‖ that is, for arguing over the legitimacy or illegitimacy of specific ideas or plans (Tienari et al 2003).…”
mentioning
confidence: 99%
“…Moreover, merger studies in private industry show that executive management pro-actively uses the media as an arena to interpret, explain and argue for the legitimacy of a merger to the public (Hellgren et al, 2002;Tienari et al, 2003). In this study the Director was unable to use the media to convey management's counter-defensive message.…”
Section: External Actors Entering the Conflictmentioning
confidence: 99%